Geochemistry of sediments in Crepin point: Towards environmental base line in Machu Picchu Peruvian Antarctic station. King George Island - Cerpa Cornejo, Luis Moroni (2016)
Documento presentado en Conference XXXIV SCAR 'Antarctica in the Global Earth System: From the Poles to the Tropics', Kuala Lumpur, 20-30 August 2016.